Risk of suicide in a sample of Egyptian high school adolescent students: a cross-sectional study - Eman S. Rabie; Marwa Soltan; Hanan Elrassas; Atteya Khairy; Moatazbellah I. Ali (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background A lethal incident of self-harm with desire to die is called suicide. Every year, suicide claims the lives of more than 800,000 individuals globally. Teenagers and younger adults commit suicide on a regular basis. In late childhood and early adulthood, it is one of the primary triggers of death. Negative social and economic consequences and negative psychological consequences have been linked to it. The objective of this study was to determine the frequency and risk factors of suicidal ideation and behavior in adolescents’ students attending high school in Cairo. Throughout the educational year (September 2021 to June 2022), a cross-sectional study was carried on 553 students. A detailed medical and sociodemographic information were obtained. The Suicide Possibility Scale (SPS) was used to assess the likelihood of suicide, while the General Health Questionnaire (GHQ-28), which consists of 28 items, was used to assess the likelihood of mental illness. Results Screening among 553 high school students, it was shown that 11.03 percent of high school students were likely to have suicidal ideas or attempted suicide (scores ≥ 25) based on the SPS (Arabic version); females were more probable to do so (12.9 percent) than males (8.2%). Results from the Arabic version of GHQ_28 survey showed that 17.54% of the assessed students had a moderate to high risk of having a mental illness issue (scores < 7). There was a significant positive correlation among the total GHQ-28 score and various SPS score components for students in their first, second, and third grades level. Age, non-suicidal self-injury, and positive personal history of suicidal ideas for the student in the whole study group were non-significantly correlated (P > 0.05) with larger Suicide Probability Scale scores. While positive personal history of suicidal attempts, positive psychiatric illnesses and positive family history of suicide showed a significant correlated (P ≤ 0.05) with larger Suicide Probability Scale scores. Conclusions Screening among adolescent high school students found that 11.03% of them had a probable risk of suicide with higher risk in females than in males that increased with age. Risk of suicide among students was associated with history of attempted suicide and psychiatric illness. So, early detection and management of students with psychiatric illness could decrease risk of suicide among them.